Impact of Financial Literacy on Financial Wellbeing Among Generation Z in Pokhara (Janapriya Journal of Interdisciplinary Studies, 2025)
In an era of increasing financial complexity and digital transformation, financial literacy has become essential for ensuring individual financial stability and well-being. Generation Z, being the most tech-savvy yet financially inexperienced cohort, faces unique challenges in navigating modern financial systems. In emerging urban centers like Pokhara, Nepal, where youth participation in financial activities is rising, understanding how financial literacy shapes financial well-being is increasingly important. This study explores the impact of six core dimensions of financial literacy namely financial knowledge, experience, skills, behavior, awareness, and attitude on the financial well-being of Generation Z in Nepal. A structured questionnaire was used to gather primary data from young individuals actively engaged in financial decision-making. The research employed descriptive statistics, correlation, and regression analyses to examine the relationships between variables. The results reveal that financial awareness is the most influential factor driving financial well-being, followed by financial experience and financial attitude. Financial behavior and knowledge also contribute positively, albeit to a lesser extent, while financial skills do not show a significant effect. These findings suggest that a deeper understanding of financial tools, combined with real-life financial exposure and a positive money mindset, plays a more critical role in enhancing financial well-being than technical skill alone. The study provides useful insights for educators, financial institutions, and policymakers aiming to strengthen financial capability among youth in emerging market contexts.Keywords: , , , ,Generation Z.